Dynamic strain and β-catenin mediated suppression of interferon responsive genes in quiescent mesenchymal stromal/stem cells - Parisa Dashti; Eric A. Lewallen; Gary S. Stein; Bram C.J. van der Eerden; Johannes P.T.M. van Leeuwen; Andre J. van Wijnen (Biochemistry and Biophysics Reports)
Multipotent bone marrow mesenchymal stromal/stem cells (MSCs) respond to mechanical forces. MSCs perceive static and dynamic forces through focal adhesions, as well as cytoskeletal and intranuclear actin. Dynamic strain stimulates nuclear β-catenin (Ctnnb1) that controls gene expression and suppresses osteogenesis. The sensitivity of MSCs to external mechanical forces may be altered by cessation of proliferation, when MSCs begin to express extracellular matrix (ECM) proteins and generate cell/cell contact. Therefore, we assessed whether and how gene expression of proliferating versus quiescent MSCs responds to mechanical stimuli. We used RNA-seq and RT-qPCR to evaluate transcriptomes at 3 h after dynamic strain (200 cycles × 2 % for 20 min) once daily during a two-day time course in naïve (uninduced) MSCs. Transcriptomes of untreated MSCs show that cells become quiescent at day 2 when proliferation markers are downregulated, and ECM related genes are upregulated. On both day 1 and day 2, dynamic strain stimulates expression of oxidative stress related genes (e.g., Nqo1, Prl2c2, Prl2c3). Strikingly, in quiescent MSCs, we observe that dynamic strain suppresses multiple interferon (IFN) responsive genes (e.g., Irf7, Oasl2 and Isg15). IFN responsive genes are activated in MSCs depleted of β-catenin using siRNAs, indicating that β-catenin normally suppresses these genes. Our data indicate that the functional effects of dynamic strain and β-catenin on IFN responsive genes in MSCs are mechanistically coupled. Because dynamic strain and β-catenin reduce the osteogenic potential of MSCs, our findings suggest that IFN responsive genes are novel biomarkers and potential regulators of mechanical responses at early stages of lineage-commitment in post-proliferative MSCs.